Krytyka . kwartalnik polityczny, no. 5, 1979 - [EIC Stefan Starczewski], apart from EIC the list of ed. committee members: Konrad Bieliński, Miklos Haraszti (Hungary), Vaclav Havel (Czechoslovakia) [et al.] (Niezależna Oficyna Wydawnicza Nowa], 1979)
Creation and circulation: From issue no. 34/35(1991) published legally